Bioactivity‐based molecular networking‐guided identification of guttiferone J from Garcinia cambogia as an anti‐obesity candidate. (22nd November 2022) - Feng, Zheling; Chen, Jiali; Chen, Cheng; Feng, Lu; Wang, Rui; Zhu, Jianzhong; Lou, Ruohan; Liu, Jia; Ye, Yang; Lin, Ligen
Abstract : Background and Purpose: Pharmacological intervention to induce browning of white adipose tissue provides a promising anti‐obesity therapy. The fruits of Garcinia cambogia (Clusiaceae) have been widely applied to manage body weight; however, the chemical principles remain unclear. The current study aims to discover browning inducers from the fruits of G. cambogia and investigate the underlying mechanisms. Experimental Approach: The bioactivity‐based molecular networking and Oil Red O staining on 3T3‐L1 and C3H10T1/2 adipocytes were applied for guided isolation. High‐fat diet‐induced obese mice were recruited to evaluate the anti‐obesity activity. Key Results: The bioactivity‐based molecular networking‐guided isolation yielded several polycyclic polyprenylated acylphloroglucinols from the fruits of G. cambogia with lipid‐lowering effect in adipocytes, including guttiferone J (GOJ), garcinol and 14‐deoxygarcinol. As the most potent one, GOJ (10 μM) reduced lipid accumulation by 70% and 76% in 3T3‐L1 and C3H10T1/2 adipocytes, respectively. Furthermore, GOJ (2.5–10 μM) increased the expression of the deacetylase sirtuin 3 (SIRT3) and activated it, which, in turn, reduced the acetylation level of PPARγ coactivator‐1α to boost mitochondrial biogenesis and promoted uncoupling protein 1 expression to enhance thermogenesis, resulting in browning of adipocytes. In high‐fat diet‐induced‐obese mice, GOJ (10 and 20 mg·kg −1 ·day −1 for 12 weeks) protected against adiposity, hyperlipidaemia, insulin resistance and liver lipotoxicity, through boosting SIRT3‐mediated browning of inguinal adipose tissue. Conclusion and Implications: GOJ represents a new scaffold of thermogenic inducer, which is responsible for the anti‐obesity property of G. cambogia and can be further developed as a candidate for treating obesity and its related disorders. Abstract : Guttiferone J was identified as a thermogenic inducer through bioactivity‐based molecular networking‐guided isolation, which is responsible for the anti‐obesity property of Garcinia cambogia .